Free Gingival Graft to Increase Keratinized Mucosa after Placing of Mandibular Fixed Implant-Supported Prosthesis - Danny Omar Mendoza Marin; Andressa Rosa Perin Leite; Lélis Gustavo Nícoli; Claudio Marcantonio; Marco Antonio Compagnoni; Elcio Marcantonio (Case Reports in Dentistry)
Insufficiently keratinized tissue can be increased surgically by free gingival grafting. The presence or reconstruction of keratinized mucosa around the implant can facilitate restorative procedure and allow the maintenance of an oral hygiene routine without irritation or discomfort to the patient. The aim of this clinical case report is to describe an oral rehabilitation procedure of an edentulous patient with absence of keratinized mucosa in the interforaminal area, using a free gingival graft associated with a mandibular fixed implant-supported prosthesis. The treatment included the manufacturing of a maxillary complete denture and a mandibular fixed implant-supported prosthesis followed by a free gingival graft to increase the width of the mandibular keratinized mucosa. Free gingival graft was obtained from the palate and grafted on the buccal side of interforaminal area. The follow-up of 02 and 12 months after mucogingival surgery showed that the free gingival graft promoted peri-implant health, hygiene, and patient comfort. Clinical Significance. The free gingival graft is an effective treatment in increasing the width of mandibular keratinized mucosa on the buccal side of the interforaminal area and provided an improvement in maintaining the health of peri-implant tissues which allows for better oral hygiene.